Functionalisation of rice bran assisted by ultrasonication and fermentation for the production of rice bran–lingonberry pulp‐based probiotic nutraceutical. (15th April 2021) - Vaitkeviciene, Ruta; Zadeike, Daiva; Gaizauskaite, Zydrune; Valentaviciute, Kristina; Marksa, Mindaugas; Mazdzieriene, Ramute; Bartkiene, Elena; Lele, Vita; Juodeikiene, Grazina; Jakstas, Valdas
Summary: A probiotic nutraceutical based on functionalised rice bran (RB) supplemented with lingonberry ( Vaccinium vitis‐idaea  L.) pulp (LP) at various levels (10–50 g/100 g d.w.) was developed. Prior to immobilisation of lactic acid bacteria (LAB) cells, RB‐LP matrix was structured by ultrasound (US) (850 kHz; power 160 W) for 20 min at 40 °C. Xanthan gum and sodium alginate were used for the stabilisation of RB‐LP matrix. Survival and fermentative activity of the immobilised LAB cells was studied by monitoring pH, cell number, antimicrobial activity, lactic acid and acetic acid production. US treatment increased by 17.5% soluble dietary fibre (SDS) contents in RB but reduced on average by 49.9% hyperoside, quercetin, quercitrin and coumaric acid contents in LP material. RB substrate supplemented with LP (20–50 g/100 g d.w.) resulted in higher antimicrobial activity against Escherichia coli, Salmonella typhimurium and Staphylococcus aureus for Lactobacillus brevis, and against Bacillus cereus and Staphylococcus aureus for Pediococcus acidilactici . RB‐LP matrix stabilised with alginate–xanthan and alginate maintained 8.09–8.67 log CFU g −1 live cells of immobilised L .  brevis after 7 weeks of storage at 4 °C. In the case of protection under simulated in vitro digestion conditions, RB‐LP gels with sodium alginate demonstrated the highest cell survival with 4.25 CFU g −1 viable cells remaining in the product and 5.23 log CFU g −1 live cells in the digestion medium. Abstract : A probiotic nutraceutical based on functionalised rice bran (RB) supplemented with lingonberry (Vaccinium vitis‐idaea L.) pulp (LP) and probiotic lactic acid bacteria (LAB). RB‐LP matrix was structured by ultrasound (US) (850 kHz; power 160 W) for 20 min at 40 °C. Xanthan gum and sodium alginate were used for the stabilisation of RB‐LP matrix.